مراحل تطوير اللغة وتصييغ اللهجات لماذا يجب أن يحظى العالم بجميع اللغات والثقافات؟ - Muhammad Azhar (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
Language is a human characteristic and is a natural talent that adorn the human. Language is often interpreted as a dialect, the old Arabs said that Arabic is their dialect and bad language according to them is an inappropriate dialect which has no measure and and does not include Arabic fusha. The emergence of human language or the first forms that appeared on it. It comes in the life of language, what it takes in the voices, the structure of morphology, structures of syntax and breadth and narrowness and the rise and fall, and the divisions of the dialects and conflict with others, and the result of the conflict of continuity or death or predominance or widening or receding and faded before the predominance of another language , And common languages, this area is called language life (Vi Du language).